Assessment of Climate Change Impacts on Crop Water Requirements Under Gezira Scheme Condition. Sudan - Ahmed, Shamseddin Musa (Gezira Journal of Engineering and Applied Sciences; Vol 9 No 1 (2014), 2014)
Water rather than land (80 million hectare, mha) has limited the agricultural production and expansion in Sudan. Any further reduction in irrigation water availability thus would have severe detrimental impacts, especially on irrigated agriculture that is currently producing 50% of the crop yields. There is a very high confidence that the arid and semi-arid areas would suffer a decrease in water resources due to climate change. The specific objective of this study is to assess the impacts of climate change on the crop water requirements (CWR) of the main grown crops in the Gezira scheme. Two approaches were used for the assessment. The first is the HADGEM2-ES climate change model approach. The second is the Change Factor approach. Both indicated decreasing trends in rainfall and the opposite holds true for temperature. Accordingly, the CWR increased by 5-45% for cotton, 9-45% for groundnut, 9-51% for sorghum, 15-52% for wheat and 4-40% for small vegetables. Consequently, with the assumption that the irrigation efficiency is 100%, the command area of the scheme (2.1 million feddan) by the year 2040 would need an ), 3km .050% (3 d byincreasewould be CWRthe total Thus, . 39 km -irrigation water supply of 6.6 which outweighs the drawn benefits of the Rosieres dam heightening project. Under the condition use of irrigation efficientthe constant remained is ) 3(18.5 kmshare in Nile water ’sSudanthe that water is the paved way to follow for bridging such tremendous expected deficit. This necessitates capacity building programs and win-win cooperation with Egypt and Ethiopia